Adsorption and Regeneration Studies for the Removal of Chromium(VI) from the Wastewater of Electroplating Industry using Granular Activated Carbon - Tandel, M.A.; Oza, B.N. (Asian Journal of Chemistry, 2016)
Batch adsorption and desorption kinetics studies were carried out on electroplating wastewater using granular activated carbon with particle size 0.51.08 mm as an adsorbent. The effect of pH, Cr(VI) concentration, adsorbent dose and contact duration were studied in batch experiments. The desorption experiments were carried out by shaking granular activated carbon saturated with Cr(VI) in (i) distilled water (27 and 50°C) and (ii) 0.1 N NaOH. A reaction time of 1 h was maintained in the regeneration study. The removal of Cr(VI) was in general most effective at low pH values. The adsorption behaviour can be explained better on the basis of Freundlich and Langmuir adsorption isotherm model.